The research and application of the collision detection algorithm in the virtual simulation system - Li, Panpan; Shan, Liang; Su, Zhiyong (Chinese Control Conference, 2014)
With the development of simulation technology, computer software and hardware technology, three-dimensional virtual simulation has been widely used in many fields. Based on Visual Studio2008 software platform and OpenSceneGraph three-dimensional scene rendering engine, this paper programs and achieves a process in which the moving car runs on the rough terrain in a virtual simulation environment. This paper designs the collision detection algorithm to deal with the collision problem about the car and the three-dimensional terrain. The simulation shows that the designed collision detection algorithm can obtain good results.